Literature Review : How to Examine the Mediating Factor of Government Role in Renewable Energy Adoption - Indri Haryani; Sri Widiyanesti; Aida Fauzia Rahmatika; Dryasmara Kusumastuty; Hendri Bhirowo; Fefria Tanbar (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2024)
Indonesia is a blessed country with abundant renewable resources and the potential to manufacture up to 419 GWh of clean electricity for its people. The government plays a crucial role in shaping and nurturing the proper environment to support RE adoption and transition toward a sustainable economy. Various tools and dimensions are available to observe the government's role in accelerating RE adoption. However, studies show that the metrics used to examine Indonesia’s government regarding RE adoption are lacking. This provides an opportunity to improve the metrics by referring to countries worldwide that show success in the particular research field. The current study aims to address the challenge by presenting a literature review of studies on the government's role in RE adoption and extracting insight to develop improved metrics for examining Indonesia’s government's role in RE adoption. Furthermore, we use data mining to visualize the research map of the current topic to provide an understanding of which areas are underexplored. Thus, future studies can refer to the results to contribute further to the literature.